Olfactory Ensheathing Cells for Spinal Cord Injury: Sniffing Out the Issues. Issue 6 (June 2018) - Yao, R.; Murtaza, M.; Velasquez, J. Tello; Todorovic, M.; Rayfield, A.; Ekberg, J.; Barton, M.; St John, J.
Olfactory ensheathing cells (OECs) are glia reported to sustain the continuous axon extension and successful topographic targeting of the olfactory receptor neurons responsible for the sense of smell (olfaction). Due to this distinctive property, OECs have been trialed in human cell transplant therapies to assist in the repair of central nervous system injuries, particularly those of the spinal cord. Though many studies have reported neurological improvement, the therapy remains inconsistent and requires further improvement. Much of this variability stems from differing olfactory cell populations prior to transplantation into the injury site. While some studies have used purified cells, others have used unpurified transplants. Although both preparations have merits and faults, the latter increases the variability between transplants received by recipients. Without a robust purification procedure in OEC transplantation therapies, the full potential of OECs for spinal cord injury may not be realised.